Fifty economic fallacies exposed - Wood, Geoffrey E., 1945- (Occasional paper (Institute of Economic Affairs (Great Britain)), 2014)
These lucid and stimulating articles are invaluable to students struggling to master some of the complexities of economic theory and its applications, who often find that the most effective way to learn economic analysis is to see such fallacies exposed. It is a text particularly suitable for first-year economic students, complementing existing textbooks as it does, and clarifying basic concepts in economics while demonstrating the practical uses of economic theory -- back cover.